2016
DOI: 10.4103/2231-0762.183102
|View full text |Cite
|
Sign up to set email alerts
|

Oral health status and treatment needs among 10126 school children in West Godavari district, Andhra Pradesh, India

Abstract: Objectives:Oral diseases are affecting a large percentage of children worldwide. This study with Indian Society of Pedodontics and Preventive Dentistry collaboration was taken up with the aim to evaluate the oral health status and treatment needs in school-going children of the West Godavari district, Andhra Pradesh, India.Materials and Methods:This cross-sectional study was conducted among 10126 school children who were randomly selected from 32 schools in West Godavari district. To find the significance of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…15.0%). [24] The reason might be due to the different sources of data collection and different protocols in the measurement of orthodontic treatment need. From the recent evidence, the interproximal caries had some relationship with the malocclusion traits such as crowding, overjet, anterior crossbite, and angle classification.…”
Section: Discussionmentioning
confidence: 99%
“…15.0%). [24] The reason might be due to the different sources of data collection and different protocols in the measurement of orthodontic treatment need. From the recent evidence, the interproximal caries had some relationship with the malocclusion traits such as crowding, overjet, anterior crossbite, and angle classification.…”
Section: Discussionmentioning
confidence: 99%
“…The total prevalence of developmental disturbances among school children in this study was 11.4%. The prevalence rates of various studies from India reported in the range of 1.8%–39.2%[ 13 14 15 16 17 18 19 20 ] [ Table 5 ]. The current study observed male predilection which was similar to published reports,[ 14 15 16 17 ] whereas fewer studies documented female predilection.…”
Section: Discussionmentioning
confidence: 99%
“…The current study observed male predilection which was similar to published reports,[ 14 15 16 17 ] whereas fewer studies documented female predilection. [ 13 18 19 20 ] This study documented 14 types of developmental anomalies that were prevalent among participants [ Table 1 ].…”
Section: Discussionmentioning
confidence: 99%
“…8 Many studies have evaluated the oral health status of schoolchildren in many parts of Tamil Nadu and also other places of India, but no studies reported on the oral health status of Thanjavur children, hence the present cross-sectional study was conducted among 204 schoolchildren of both private-and government-sector schools (Table 1). 8 Chidambaram, Tamil Nadu 5-15 63.83% Sukhabogi et al 10 Hyderabad, Andhra Pradesh 12 41.4% Good oral hygiene-39.1% 15 Poornima et al 11 Davanagere city, Karnataka 8-9 60.1% Kalaskar et al 12 Vidarbha region, Maharashtra 6-16 65.70% Arora and Bhateja 13 Mathura city, Uttar Pradesh 12 57% 84%-good oral hygiene; 16%-fair oral hygiene Behal et al 14 Kashmir, J & K 6-12 45.48% 42.8% good oral hygiene Prasad et al 15 West Godavari district, Andhra Pradesh 11-14 63.5%…”
Section: Discussionmentioning
confidence: 99%